2021
DOI: 10.3389/fpsyg.2021.618507
|View full text |Cite
|
Sign up to set email alerts
|

Morality and Values in Sports Among Young Athletes: The Role of Sport Type and Parenting Styles – A Pilot Study

Abstract: Given the great importance of morality and values in modern sports, especially among young athletes, in this pilot study, we sought to broaden the exploration of the factors that may play role in these contexts, which have not been widely researched to date. Accordingly, the study tested the relationships between sport type (team or individual) and parenting styles (authoritative vs. non-authoritative), and moral decision-making in sport and sport values among 110 adolescent athletes whose age ranges from 11 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Our study corroborates previous research emphasizing the social, psychological, and well-being benefits of sports among students [15,38]. It indicates that sports encourage social interactions, foster a sense of belonging, and instill important behavioral habits [39,40]. Therefore, participants engaging in sports at any level experience these benefits, contributing to their overall college experience.…”
Section: Discussionsupporting
confidence: 89%
“…Our study corroborates previous research emphasizing the social, psychological, and well-being benefits of sports among students [15,38]. It indicates that sports encourage social interactions, foster a sense of belonging, and instill important behavioral habits [39,40]. Therefore, participants engaging in sports at any level experience these benefits, contributing to their overall college experience.…”
Section: Discussionsupporting
confidence: 89%
“…All sports can provide an opportunity for participants to develop their moral character, although these impacts vary among different kinds of sports. Yaffe et al (29) noted that participants in team sports tend to tolerate more cheating and gamesmanship than do participants in individual sports. Team (vs. individual) athletes tend to value status in sports relatively more, while individual (vs. team) athletes tend to value competence relatively more.…”
Section: Practicality Of Sports Moral Charactermentioning
confidence: 99%
“…Team (vs. individual) athletes tend to value status in sports relatively more, while individual (vs. team) athletes tend to value competence relatively more. In addition, Yaffe et al (29) also highlighted the differences among individual sports. Sanlav and Donuk (30) found that track and field as well as tennis athletes demonstrate more integrity, compassion, sportspersonship, and fairness than do other athletes.…”
Section: Practicality Of Sports Moral Charactermentioning
confidence: 99%
“…Psychological capital can predict student performance, academic achievement level, employability, etc. It can also predict student mental health, emotion regulation, and emotion management ( Yaffe et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%